The new climate war the fight to take back our planet - Mann, Michael E. 1965- (Scribe, 2021)
Recycle. Fly less. Eat less meat. These are some of the tactics that we've been told can slow climate change. But most of these recommendations are a result of a multi-pronged marketing campaign that has succeeded in placing the responsibility for fixing climate change squarely on the shoulders of individuals. Fossil fuel companies have followed the example of other industries deflecting blame (think "guns don't kill people, people kill people") or greenwashing (think of the beverage industry's "Crying Indian" commercials of the 1980s)
Keywords: Verantwortungsethik; Umweltpolitik; Klimaänderung; Environmental policy / Citizen participation; Climatic changes / Government policy / Citizen participation; Global warming / Prevention